M. ‘Teresita Lantin-Rosario’ and M. ‘Dolores A. Ramirez’ – new varieties of Mussaenda - Antesco, Gerlie P.; Bengoa, Jennelyn C.; Guevarra, Maria Luisa D. (2023)
An outstanding selections of Mussaenda developed at the Institute of Plant Breeding (IPB), College of Agriculture and Food Science (CAFS), University of the Philippines Los Baños (UPLB) were registered to the National Seed Industry Council as new varieties. These are Mussaenda ‘Teresita Lantin-Rosario’ and Mussaenda ‘Dolores A. Ramirez’, named after an ornamental plant breeder and a National Scientist, respectively, in recognition of their significant contributions to the fields of genetics and plant breeding. Mussaenda ‘Teresita Lantin-Rosario’ is a hybrid and a progeny from a cross between M. ‘Maria Makiling’ and M. ‘Diwata’. The calyx lobes are all petaloid, numerous, and hairy. Petaloids are creamy white (157C) with visible midrib and pale yellow-green veins underneath, are ovate to suborbicular in shape, and are 5.0–9.3 x 3.7–7.5 cm in size. M. ‘Dolores A. Ramirez’ is also a hybrid from the cross M. ‘Maria Makiling x M. ‘Doña Trining’. The calyx lobes are all petaloid, two to three of which are more enlarged while the rest are partially expanded in a cluster, are elliptic-lanceolate to ovate-orbicular in shape, 4.5 ˗ 9.0 x 0.3 ˗ 6.2 cm in size, and are empire rose (48A) with prominent pinkish white veins above and orient pink (36D) below with a tinge of yellow-green (145A) towards the apex.
Keywords: Mussaenda (plant)